2010
DOI: 10.4314/sajhe.v23i3.51017
|View full text |Cite
|
Sign up to set email alerts
|

Career counselling in the 21st century: South African institutions of higher education at the crossroads

Abstract: The current state of career counselling 1 in South African institutions of higher education in the 21st century is explored in this article in an attempt to locate current work in the field of career counselling in South Africa in the light of global trends (academic and economic) and in terms of local history and current economic climate. The article is based largely on an examination of factors that have contributed collectively and individually to the current state of affairs in career counselling in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…This has become increasingly more apparent in the past few years. Counsellors' 'expert' role in the career facilitation process, prior to the development of a global economy, often disempowered clients (Maree, 2009). Clients were often likely to be excluded from the decision-making process and in doing so gave the counsellors full control over choices that are made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has become increasingly more apparent in the past few years. Counsellors' 'expert' role in the career facilitation process, prior to the development of a global economy, often disempowered clients (Maree, 2009). Clients were often likely to be excluded from the decision-making process and in doing so gave the counsellors full control over choices that are made.…”
Section: Introductionmentioning
confidence: 99%
“…Maree and Pollard (2009) state that contemporary society is characterized by the rapid advancements in information technologies and globalization, which heralded the start of the twenty-first century. A need for the development of innovative skills and changes in attitude towards work requirements has arisen in response to these rapid advancements (Maree, 2009). Savickas et al (2009) argue that it is becoming increasingly challenging to predict what the future holds for individuals in a globalized world.…”
Section: Introductionmentioning
confidence: 99%
“…While studies conducted in other South African higher education institutions attest that counselling provide support to students on a wide range of topics such as relationships, career selection, mental health and social problems that may hinder student success and retention (De Jager,Ntlokwana, 2012;Hartung, 2009, Maree, 2009, culture seem to inhibit or enable the use of counselling services (Maree, 2002, Norton, 2002. In this study, the fact that 35% (80) indicated that they could not share problems with anyone points to the belief that anyone who is not able to solve their own problem is weak.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Since counseling involves several meetings with counselor to discuss issues of concern, clients who do not clearly understand the language used during the counseling sessions find it uncomfortable to discuss with counselor. To this end, Maree (2009) contends that psychometric testing instruments largely cater for communities who speak English as first language. In a multi-lingual country like South Africa, this scenario, therefore, segregates majority of the students whose first language is not necessarily English.…”
Section: Background and Introductionmentioning
confidence: 99%
“…The practicalities of the 21st-century labour market should co-determine assessment strategies, and theory development should integrate benchmark concepts such as internationalization, globalization of the workforce, labour surplus, downsizing, outsourcing, corporate reorganization, diversification, lifelong learning, multi-skilling, and the acquisition of information communication technology skills (Maree, 2009). Intervention should aim at enhancing students' employability, improving their career adaptability, and helping them assume authorship of their career and life stories.…”
Section: Developing New Assessment Instrumentsmentioning
confidence: 99%